Dynamic Characteristics And Seismic Performance Of Reinforced Concrete Buildings Experiencing 5 June 2015 And 8 March 2018 Sabah Earthquakes - Ho, Kar Meng (Universiti Sains Malaysia, 2019)
Staff quarters of S.M.K. Ranau and officer quarters of Hospital Ranau that were damaged during a Sabah earthquake with a magnitude of 6.0 on 5 June 2015 were repaired in 2016. However, an earthquake with a magnitude of 5.2 struck Ranau, Sabah again on 8 March 2018, thus it is unknown for the present condition of both buildings. This dissertation presents the results on dynamic characteristics of these buildings experiencing both Sabah earthquake events based on microtremor observations in January 2016, April 2017 and November 2018. The modal frequencies and vibration mode shapes of the buildings were determined by using the Nakamura method and Time Domain Decomposition method, respectively. Due to the absence of the study on dynamic characteristics of both buildings before 2015 Sabah earthquake, computational analyses were performed using ETABS based on the architectural plan and on-site measurement in order to simulate the building condition before the earthquake. The results show that the fundamental frequencies for staff quarters of S.M.K. Ranau and officer quarters of Hospital Ranau reduced up to 20 % after 2015 Sabah earthquake. This reduction is significant and consistent with moderate damages suffered by both buildings. For the case after 2018 Sabah earthquake, the fundamental frequencies of both buildings reduced less than 2.5 %. This implies that both buildings may suffered very minor damages during the earthquake. Seismic performances of both buildings under the design load stipulated in Malaysia National Annex to MS EN 1998-1:2015 were obtained through numerical simulation by using modal response spectrum analysis. Under the design acceleration of 0.16 g, the maximum interstorey drift occurs at the first floor due to soft storey effect. The maximum interstorey drift for the staff quarters of S.M.K. Ranau exceeded the damage limitation as specified in Eurocode 8. The results also showed that the column jacketing applied to staff quarters of S.M.K. Ranau during repair in 2016 increased the fundamental frequency and reduced the maximum storey displacement and interstorey drift, but this also increased the maximum storey shear force and overturning moment at the ground floor.